Blind People Stick Tracking Using Android Smartphone and GPS Technology - Rian Adi Chandra; Umi Fadlillah; Prasetyo Wibowo; Faizal Tegar Nanda Saputra; Reyhan Radditya Sulasyono (Khazanah Informatika, 2022)
Blindness is a term to describe conditions of people who have visual impairments. When a visually impaired do an activity outside, he usually needs a stick to help them move. This study aims to develop a stick tracking that enable a family member to find the location of the blind when they are outside their home and can help the blind to travel. GPS (Global Positioning System) technology allows the stick to get a signal for its location coordinates. When a family member wants to get the location of the blind, he can send a text message with the keyword TRACKER to the mobile phone number of the stick. A GSM (Global System for Mobile Communication) module will send a reply containing the global coordinate, which Google Maps can visualize. In addition, the blind can actively send an emergency help signal to families if they have difficulty finding their way home. An emergency push button is available on the stick, which, if pressed, will send the coordinates to the family's phone number in the form of a short text message. During travelling, blind people can identify obstacles in front of them thanks to an ultrasonic sensor system on the stick. The sensor can detect an object in the range of 100 cm. If the sensor detects an object less than 100 cm, a buzzer will emit an edible sound for the blind. Observations show that the developed stick works well with an average error on the GPS module at a level of 11.89 meters. It also shows a fluctuating percentage of ultrasonic sensor errors depending on the distance of objects.